Drinking water is a significant predictor of Blastocystis infection among rural Malaysian primary schoolchildren - Abdulsalam, Awatif Mohamed; Ithoi, Init; Al-Mekhlafi, Hesham Mahyoub; Ahmed, Abdulhamid; Surin, Johari; Mak, Joon Wah (Cambridge University Press, 2012)
Blastocystis infection has a worldwide distribution especially among the disadvantaged population and immunocompromised subjects. This study was carried out to determine the prevalence and the association of Blastocystis infection with the socio-economic characteristics among 300 primary schoolchildren, living in rural communities in Lipis and Raub districts of Pahang state, Malaysia. Stool samples were collected and examined for the presence of Blastocystis using direct smear microscopy after in vitro cultivation in Jones' medium. The overall prevalence of Blastocystis infection was found to be as high as 25·7%. The prevalence was significantly higher among children with gastrointestinal symptoms as compared to asymptomatic children (x2=4·246; P=0·039). Univariate and multivariate analyses showed that absence of a piped water supply (OR=3·13; 95% CI=1·78, 5·46; P<0·001) and low levels of mothers’ education (OR=3·41; 95% CI=1·62, 7·18; P<0·01) were the significant predictors of Blastocystis infection. In conclusion, Blastocystis is prevalent among rural children and the important factors that determine the infection were the sources of drinking water and mothers' educational level. Interventions with provision of clean water supply and health education especially to mothers are required.